PROSES MANUFAKTUR MESIN GERGAJI KAYU UNTUK PENGRAJIN PALET KAYU - Akhmad Syarief; Akhmad Maulana Gumai (Mechanical Engineering Department, Faculty of Engineering, Universitas Lambung Mangkurat, 2017)
Wood saws are hand machines that small industries need. Almost all work processes through a saw machine with good results. Circular saws are not only used in timber industry, but also in the carbuery industry, by plumbing, construction experts, loggers or gardenists. In any hobby there are wearing it. For manufacturing process of making wood sawing machine in allotment for wooden pallet craftsman. The formulation of the problem in making this saw machine is how to manufacture wood saw process for wooden pallet craftsman and howmuch budget cost in manufacturing process of saw machine for wooden pallet craftsman. The components of the saw machine are frame, table mat, bearing, shaft, pulley transmission and V belt, while the tools and machinery used in the manufacturing process are electric welding tools, electric grinding wheels, grinding wheels, lathes, and frais machines.